Post-transcriptional regulation of ribosome biogenesis in yeast - Isabelle C. Kos-Braun; Martin Koš (Microbial Cell, 2017)
Most microorganisms are exposed to the constantly and often rapidly changing environment. As such they evolved mechanisms to balance their metabolism and energy expenditure with the resources available to them. When resources become scarce or conditions turn out to be unfavourable for growth, cells reduce their metabolism and energy usage to survive. One of the major energy consuming processes in the cell is ribosome biogenesis. Unsurprisingly, cells encountering adverse conditions immediately shut down production of new ribosomes. It is well established that nutrient depletion leads to a rapid repression of transcription of the genes encoding ribosomal proteins, ribosome biogenesis factors as well as ribosomal RNA (rRNA). However, if pre-rRNA processing and ribosome assembly are regulated post-transcriptionally remains largely unclear. We have recently uncovered that the yeast Saccharomyces cerevisiae rapidly switches between two alternative pre-rRNA processing pathways depending on the environmental conditions. Our findings reveal a new level of complexity in the regulation of ribosome biogenesis.